RNA triplexes : from structural principles to biological and biotech applications - Devi, Gitali (2015)
The diverse biological functions of RNA are determined by the complex structures of RNA stabilized by both secondary and tertiary interactions. An RNA triplex is an important tertiary structure motif that is found in many pseudoknots and other structured RNAs. A triplex structure usually forms through tertiary interactions in the major or minor groove of a Watson–Crick base-paired stem. A major-groove RNA triplex structure is stable in isolation by forming consecutive major-groove base triples such as U·A-U and C+·G-C. Minor-groove RNA triplexes, e.g., A-minor motif triplexes, are found in almost all large structured RNAs. As double-stranded RNA stem regions are often involved in biologically important tertiary triplex structure formation and protein binding, the ability to sequence specifically target any desired RNA duplexes by triplex formation would have great potential for biomedical applications. Programmable chemically modified triplex-forming oligonucleotides (TFOs) and triplex-forming peptide nucleic acids (PNAs) have been developed to form TFO·RNA2 and PNA·RNA2 triplexes, respectively, with enhanced binding affinity and sequence specificity at physiological conditions. Here, we (1) provide an overview of naturally occurring RNA triplexes, (2) summarize the experimental methods for studying triplexes, and (3) review the development of TFOs and triplex-forming PNAs for targeting an HIV-1 ribosomal frameshift-inducing RNA, a bacterial ribosomal A-site RNA, and a human microRNA hairpin precursor, and for inhibiting the RNA–protein interactions involving human RNA-dependent protein kinase and HIV-1 viral protein Rev. WIREs RNA 2015, 6:111–128. doi: 10.1002/wrna.1261